THE RELATIONSHIP BETWEEN FEAR OF DEATH AND MEANING OF LIFE IN NURSING STUDENTS AND NURSES CARING FOR TERMINAL PATIENTS - Fidan Karadeniz; Funda Gümüş; Merve Akarslan (International Journal of Health Services Research and Policy)
IThis study aims to determine the relationship between fear of death and the meaning of life in nursing students and nurses caring for terminally ill patients. The study was conducted in a cross-sectional and relationship-seeking research design. The research was conducted between March 15 and June 30, 2023. 123 nurses and 139 nursing students working with terminal-stage patients at a university hospital participated in the study. The study was conducted with a total of 262 participants.The Personal Information Form was collected using the Fear of Death Scale (DAS) and the Meaning of Life Scale (MLQ). The relationship between fear of death and the meaning of life in nursing students and nurses caring for terminally ill patients was determined to be 31.74 (7.13) years old on average for the nurses participating in the study and 22.71 (1.66) years for the nursing students. 61% of nurses and 66.2% of nursing students were women. It was determined that 56.1% of the nurses had undergraduate degrees and 77.7% of the students were third-year students. According to the Student t-test analysis, a significant difference was detected between the groups in terms of the total score of the DAS, and the DAS scores of the nursing students were statistically significantly higher. According to the Pearson correlation analysis, a weak negative relationship was detected between the total scores of the nurses' DAS and MLQ, while no significant difference was found between the scale scores of the nursing students. In this study, the Cronbach's alpha coefficient of the Death Anxiety Scale (DAS) was found to be 0.96 and the Meaning of Life Scale (MLQ) was 0.68. It can be said that there is no relationship between the fear of death and the meaning of life in nursing students who care for terminal patients, but there is a relationship between the fear of death and the meaning of life in nurses.